Biosensors : a practical approach - Cooper, Jonathan M., 1961-; Cass, A. E. G. (Oxford University Press, 2004)
Annotation Over the past 20 years, the field of biosensor research have had a significant impact in both laboratory research and the commercial sector. Over that period, biosensors have revolutionised the care and management of diabetes and have had important impacts in several other areas of clinicaldiagnostics. Europe, North America and Asia-Pacific have all seen the rise of small and medium sized companies seeking technical and application niches in the manufacture or use of biosensors. The current activity in both gene and protein 'biochips' can be seen as the latest set of tools that allowusers who are not analytical science practitioners to make technically complex and reliable measurements with the minimum of intervention. Similarly the concern about the dissemination of chemical or biological weapons and the need for their rapid and reliable detection will need to be met bydevices that have many characteristics in common with biosensors. This book provides a practical introduction to the many skills needed in the highly interdisciplinary field of biosensor technology. Edited by two internationally renowned experts in this field it draws together contributions from active researchers in Europe, North America and Asia who describe howto implement techniques as diverse as protein engineering, optical and electrochemical instrumentation, single cell electrophysiology, screen printing and numerical modelling in the context of producing biosensors for both laboratory and commercial applications. As well as the many detailedprotocols and experimental tips, the book also offers an overview of current research in this area as well as pointers to its further directions. The diversity of topics covered means that it will be suitable both for those already active in the area who wish to expand their repertoire ofexperimental tools and for those who are just starting out in biosensors research.
Keywords: Biosensors.; elektronické knihy; electronic books